Rice Distribution Pattern: A Study on Food Security in South Kalimantan - Akbar RM Aries; Wibowo Dwi Alan; Rahmi Alia; Prabawa Sigit (Agroindustrial Journal, 2020)
In recent years, South Kalimantan has experienced rice surplus and been appointed as one of the nation’s rice barns. However, the distribution pattern of rice produce in the province is not clearly described. The distribution pattern itself plays an important role in the context of rice availability and food security. The study is aimed at investigating the rice distribution pattern in South Kalimantan. The method used was supply-demand model with system dynamics approach. Price was the experimental variable. Initially, the stakeholder roles were investigated, followed by the development of causal loop diagram (CLD), stock and flow diagram (SFD), validation, verification, and finally simulations. South Kalimantan rice supply chain is generally operated by farmers, village middleman, larger collectors, rice millers, urban wholesalers (distributors), retail sellers, and consumers. The distribution pattern is influenced by the location of rice producing area, the location of large miller/collector/wholesaler area, rice variety, and consumer preferences.